2016
DOI: 10.4172/2153-0769.1000184
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Cofactor and Sulfite Oxidase Deficiency

Abstract: A universal molybdenum-containing cofactor is necessary for the activity of all eukaryotic molybdoenzymes. In humans four such enzymes are known: Sulfite oxidase, xanthine oxidoreductase, aldehyde oxidase and a mitochondrial amidoxime reducing component. Of these, sulfite oxidase is the most important and clinically relevant one. Mutations in the genes MOCS1, MOCS2 or GPHN -all encoding cofactor biosynthesis proteins -lead to molybdenum cofactor deficiency type A, B or C, respectively. All three types plus mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Mutation in any of these genes causes deterioration in molybdenum formation. The most common mutation observed is in the MOCS1 gene, followed by the MOCS2 gene [3] . Neuronal damage is rapidly progressive and severe as a result of the accumulation of toxic concentrations of sulfite in the brain [4] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation in any of these genes causes deterioration in molybdenum formation. The most common mutation observed is in the MOCS1 gene, followed by the MOCS2 gene [3] . Neuronal damage is rapidly progressive and severe as a result of the accumulation of toxic concentrations of sulfite in the brain [4] .…”
Section: Discussionmentioning
confidence: 99%
“…The global incidence of MCD is likely to be higher as a result of failure to diagnose and under-reporting [2] . The neurologic injury caused by MCD is not fully understood [3] . It is considered that elevated levels of neurotoxic metabolites (sulfite and taurine) or the deficit of the product sulfate are cause of neurologic injury [6] .…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, sulfate is inactive and the urinary excretion pathway for endogenous and exogenous formed sulfates is well characterized. Although this is the principal pathway of sulfites bio‐metabolism, it was observed that they may be involved in alternative bioreactions, which lead to the formation of reactive forms of sulfur oxide (i.e., sulfur trioxide radical, •SO 3 − ) and also protein S‐sulfonates (Reiss, 2016).…”
Section: Chemical and Biochemical Propertiesmentioning
confidence: 99%
“…A hallmark of both diseases is the fast and progressive neurodegeneration. Patients present seizures, focal epileptic discharges, frequent vomiting and, if surviving the neonate period of life, suffer from severe mental retardation . Recently, we have shown that the sulphite‐derived metabolite S‐sulpho‐cysteine (SSC) is a main contributor to neuronal cell death .…”
Section: Introductionmentioning
confidence: 99%
“…Patients present seizures, focal epileptic discharges, frequent vomiting and, if surviving the neonate period of life, suffer from severe mental retardation. [9][10][11] Recently, we have shown that the sulphite-derived metabolite S-sulpho-cysteine (SSC) is a main contributor to neuronal cell death. 12 As structural analogue to the neurotransmitter glutamate, SSC is able to bind and activate NMDA receptors resulting in uncontrolled calcium influx and excitotoxicity within neurons.…”
Section: Introductionmentioning
confidence: 99%